2009
DOI: 10.1021/tx900329b
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Chemical Origins of Cross-Reactive Immunological Reactions to Arylamine Benzenesulfonamides: T-Cell Responses to Hydroxylamine and Nitroso Derivatives

Abstract: Exposure to sulfamethoxazole (SMX) is associated with T-cell-mediated hypersensitivity reactions in human patients. T-cells can be stimulated by the putative metabolite nitroso SMX, which binds irreversibly to protein. The hydroxylamine and nitroso derivatives of three arylamine benzenesulfonamides, namely, sulfamethozaxole, sulfadiazine, and sulfapyridine, were synthesized, and their T-cell stimulatory capacity in the mouse was explored. Nitroso derivatives were synthesized by a three-step procedure involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Auto-oxidation generates SMX-NO, self-conjugation generates azo and azoxy dimers, and reduction through enzymatic reactions or glutathione-dependent processes liberates a hydroxylamine and the parent drug ( Fig. 1) (26,34,(40)(41)(42)(43). Although these reactions result in rapid (within 5 min) and complete degradation of SMX-NO, multiple meta-stable protein adducts that become internalized via a caveole-dependent mechanism (16,44,45) are readily detectable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auto-oxidation generates SMX-NO, self-conjugation generates azo and azoxy dimers, and reduction through enzymatic reactions or glutathione-dependent processes liberates a hydroxylamine and the parent drug ( Fig. 1) (26,34,(40)(41)(42)(43). Although these reactions result in rapid (within 5 min) and complete degradation of SMX-NO, multiple meta-stable protein adducts that become internalized via a caveole-dependent mechanism (16,44,45) are readily detectable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using lymphocytes from SMX-hypersensitive patients and animal models of SMX immunogenicity demonstrated that Ag-stimulated T cells secrete high levels of the Th2 cytokine IL-5 and the Th1 cytokine IFN-g (41,47,48). Data presented in the current study using multiplex methods and cloned T cells confirm these initial reports.…”
Section: Discussionmentioning
confidence: 99%
“…4 The antibiotic group includes the sulfonarylamine antibiotics, such as sulfanilamide, sulfoxazole, and sulfamylon. 1,4,5,6 These antibiotics are structurally related with the sulfonamide moiety directly connected to a benzene ring, an amine (-NH 2 ) structure at the N4 position, and an aromatic ring at the N1 position. 1,5,6,7 It is a metabolite of the sulfonarylamines that is antigenic and elicits T-cell and IgE immunemediated reactions.…”
Section: Pathogenesismentioning
confidence: 99%
“…1,4,5,6 These antibiotics are structurally related with the sulfonamide moiety directly connected to a benzene ring, an amine (-NH 2 ) structure at the N4 position, and an aromatic ring at the N1 position. 1,5,6,7 It is a metabolite of the sulfonarylamines that is antigenic and elicits T-cell and IgE immunemediated reactions. 1,5,6 The second class, non-sulfonarylamines or sulfonamide non-antibiotics, include the carbonic anhydrase inhibitors, sulfonylureas, loop diuretics, thiazide diuretics, COX-2 inhibitors, and protease inhibitors.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation